2003
DOI: 10.1051/0004-6361:20030426
|View full text |Cite
|
Sign up to set email alerts
|

On stability of rotation of the mean magnetic field of the Sun

Abstract: Abstract. New data on the mean magnetic field of the Sun (MMFS) as a star measured at the Crimean Astrophysical Observatory in 1998-2001 are presented. The 34-year time series of the MMFS using similar data from three other observatories (1968-2001, with the total number of daily MMFS values N = 12 428), is considered. It is found that (a) the primary synodic period of the equatorial rotation of solar magnetic field, P = 26.929 ± 0.015 days, did not vary over the last 34 years, but (b) the average intensity H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…The SMMF exhibits a dominant periodicity of ≈27 days. The analysis by Haneychuk et al (2003) reported that this rotation period does not vary with time, whereas a recent study by Xie et al (2017) suggested that the rotation period of SMMF changes with the phase of the solar cycle. Besides, the amplitude of the SMMF varies slowly on the timescales of the solar cycle: being close to±2G during the sunspot maximum and±0.2G during the minimum of the solar activity (Plachinda et al 2011).…”
Section: Introductionmentioning
confidence: 88%
“…The SMMF exhibits a dominant periodicity of ≈27 days. The analysis by Haneychuk et al (2003) reported that this rotation period does not vary with time, whereas a recent study by Xie et al (2017) suggested that the rotation period of SMMF changes with the phase of the solar cycle. Besides, the amplitude of the SMMF varies slowly on the timescales of the solar cycle: being close to±2G during the sunspot maximum and±0.2G during the minimum of the solar activity (Plachinda et al 2011).…”
Section: Introductionmentioning
confidence: 88%
“…В 1968-1976 гг. двухсекторная структура вращалась с синодическим периодом P = 27.03(6) сут, но с добавлением данных он приблизился к 26.92(2) сут (Haneychuk et al, 2003). В СМ полного 52летнего ряда соответствующий пик когерентного вращения, однако, отсутствует, см.…”
Section: вращение солнцаunclassified
“…На теперiшнiй час каталог вимiрiв загального магнiтного поля Сонця в шести обсерваторiях свiту складає понад 18 тисяч добових значень. За даними спостережень i усередненими вимiрами на чотирьох обсерваторiях середня величина ЗМС складає всього 0.45 Гс, з амплiтудою змiни ЗМС в (0.22 ± 0.03) Гс [20]. Однак, як виявили цi ж дослiдники, пiврiчнi усередненi величини магнiтного поля за 34 роки спостережень показують складнi варiацiї поля в межах бiля ±0.5 Гс синхронно з 11-рiчним циклом сонячної активностi.…”
Section: магнетизм сонцяunclassified